Artes carnavalescas: processos criativos de uma carnavalesca em Belém do Pará - PALHETA, Cláudia Suely dos Anjos (Universidade Federal do Pará, 2017)
This paper presents carnival arts as expressions and artistic representations present in workshops and sheds of the samba schools during the production of a carnival parade, including plot synopses of texts, letters of samba plot, drawings, costumes and floats. This is a study based on my actions as carnavalesca in three samba schools of Belem: Academia de Samba Jurunense in 2005; Gremio Recreativo Deixa Falar in 2006, 2007, 2008 and 2009, and Associação Carnavalesca Bole-Bole in the years 2010 and 2011. From the record of memories, experiences and observations, I elaborate an autoethnography of my creative processes at the same time I try to contribute towards an ethnography of my creative processes of Carnival in Pará.